Metode Servqual dan Model IPA untuk Mengukur Kepuasan Pelanggan terhadap Pelayanan Klinik Mata Permata - Eneng Iviq Hairo Rahayu; Zahra, Zahra (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
In an era of increasingly tight competition, Permata Eye Clinic is required to provide quality medical services and service satisfaction. Unsatisfactory service can have a good impact on patient trust and loyalty, as well as affect the overall image of the clinic. The purpose of the study was to improve the quality of service and improve the performance of Permata Eye Clinic to increase patient satisfaction. The study was conducted using a questionnaire distributed to 45 respondent patients where 15 questions were used. Furthermore, data processing was carried out using the Service Quality (Servqual) method and the Importance Performance Analysis (IPA) method to determine the gap value between expectations and performance and improvements in attributes used to improve the quality of health services. The results of the study showed the average value of Servqual and the average Importance Performance Analysis (IPA), physical appearance (tangible) of 2.78 and 3.83 gap score -1.05, reliability of 2.81 and 4.00 gap score -1.19, responsiveness of 2.78 and 3.90 gap score -1.12, empathy of 2.78 and 4.03 gap score -1.25, assurance of 2.76 and 4.11 gap score -1.36. The conclusion of the calculation of the gap both per attribute and the average per dimension of SERVQUAL and the average Importance Performance Analysis (IPA) shows that all gaps are negative, which indicates that the reality received is still not by customer expectations.